Acinetobacter sp. DW-1 immobilized on polyhedron hollow polypropylene balls and analysis of transcriptome and proteome of the bacterium during phenol biodegradation process - Qihui Gu (Nature Portfolio, 2017)
Abstract Phenol is a hazardous chemical known to be widely distributed in aquatic environments. Biodegradation is an attractive option for removal of phenol from water sources. Acinetobacter sp. DW-1 isolated from drinking water biofilters can use phenol as a sole carbon and energy source. In this study, we found that Immobilized Acinetobacter sp. DW-1cells were effective in biodegradation of phenol. In addition, we performed proteome and transcriptome analysis of Acinetobacter sp. DW-1 during phenol biodegradation. The results showed that Acinetobacter sp. DW-1 degrades phenol mainly by the ortho pathway because of the induction of phenol hydroxylase, catechol-1,2-dioxygenase. Furthermore, some novel candidate proteins (OsmC-like family protein, MetA-pathway of phenol degradation family protein, fimbrial protein and coenzyme F390 synthetase) and transcriptional regulators (GntR/LuxR/CRP/FNR/TetR/Fis family transcriptional regulator) were successfully identified to be potentially involved in phenol biodegradation. In particular, MetA-pathway of phenol degradation family protein and fimbrial protein showed a strong positive correlation with phenol biodegradation, and Fis family transcriptional regulator is likely to exert its effect as activators of gene expression. This study provides valuable clues for identifying global proteins and genes involved in phenol biodegradation and provides a fundamental platform for further studies to reveal the phenol degradation mechanism of Acinetobacter sp.